1990
DOI: 10.1002/j.1460-2075.1990.tb07412.x
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic peptides of the Rab effector domain inhibit vesicular transport through the secretory pathway.

Abstract: Synthetic peptides of the putative effector domain of members of the ras‐related rab gene family of small GTP‐binding proteins were synthesized and found to be potent inhibitors of endoplasmic reticulum (ER) to Golgi and intra‐Golgi transport in vitro. Inhibition of transport by one of the effector domain peptides was rapid (t1/2 of 30 s), and irreversible. Analysis of the temporal site of peptide inhibition indicated that a late step in transport was blocked, coincident with a Ca2(+)‐dependent prefusion step.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
77
0
1

Year Published

1991
1991
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(83 citation statements)
references
References 67 publications
5
77
0
1
Order By: Relevance
“…Peptides corresponding to the effector domain of rab3, ras and rabl were synthesized as prevtously described [16]. GTPyS and GDP/JS were purchased from Boehrmger Mannheim.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Peptides corresponding to the effector domain of rab3, ras and rabl were synthesized as prevtously described [16]. GTPyS and GDP/JS were purchased from Boehrmger Mannheim.…”
Section: Methodsmentioning
confidence: 99%
“…A synthetic peptide corresponding to the putative effector domain of this SMG, except for the exchange of two amino acids (denoted rab3AL). was shown to affect intracellular vesicle transport [16].…”
Section: Introductionmentioning
confidence: 99%
“…By analogy with ras, the effector domain is believed to interact with a GAP protein, thereby stimulating the low endogenous GTPase activity of rab proteins. Effector domain peptides have, in fact, been shown to inhibit transport in the biosynthetic pathway (Plutner et al, 1990). Proteins have been identified that can escort rab proteins in the cytosol (GDI), stimulate GTP hydrolysis or facilitate GDP/GTP exchange (Huang et al, 1990;Sasaki et al, 1990;West et al, 1990;Burstein et al, 1991;Tan et al, 1991;Burstein and Macara, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…The peptide nomenclature used follows that of Plutner et al [17]. The numbering refers to the homologous amino acid positions in Ha-ras.…”
Section: Methodsmentioning
confidence: 99%